The audacity of hope thoughts on reclaiming the American Dream - Obama, Barack (New York Edinburgh, 2007)
The Audacity of Hope is Barack Obama's call for a new kind of politics a politics that builds upon those shared understandings that pull us together as Americans. Lucid in his vision of America's place in the world, refreshingly candid about his family life and his time in the Senate, Obama here sets out his political convictions and inspires us to trust in the dogged optimism that has long defined us and that is our best hope going forward.
Includes index
Keywords: Obama, Barack